PENDUGAAN PERUBAHAN STOK KARBON DI TAMAN NASIONAL BROMO TENGGER SEMERU - Rahimahyuni Fatmi Noor'an; I Nengah Surati Jaya; Nining Puspaningsih (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Recently a comprehensive source of data and information on carbon storage in various types of forest ecosystems and other land use in Java Island are still limited. This study was carried out in a conservation area of Bromo Tengger Semeru National Park (TNBTS) that represents the ecosystem types of lowland rain forest, sub-montane forests and mountain forests in Java. The information on carbon sequestration and carbon stocks at TNBTS becomes important. The main objective of this study was to estimate biomass and carbon storage in various types of forests in TNBTS using allometric approaches. The additional objectives were to estimate carbon storage on various land cover and to estimate the changes in carbon storage by land cover changes during the period 1990, 2000 and 2013. The measurement of forest carbon include aboveground, understorey, necromass and litter pools covering all ecosystem such as primary forest, secondary forest with high- and low- canopy density. This study found that the average of carbon stocks in primary forest were 193,49 ± 125,98 tonC/ha, and were 267,42 ± 119,25 tonC/ha in secondary forest. The total carbon stocks in the period 1990–2000 has decreased about 22.6 tonC/ha/year and in the period 2000–2013 has increased about 41.2 tonC/ha/year. The enhancement of carbon stocks in this area was driven by an intensive forest protection, good monitoring and land rehabilitation. Keywords: biomass, carbon storage, carbon stock, land cover, national park